Succinic acid derivatives: influence on the metabolic factors of the development of fatigue and working capacity under physical loads - Gunina, L.M.; Voitenko, V.L.; Nosach, E.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
A study has been carried out on the effect of the domestic pharmacological armadin long preparation (2-ethyl- 6-methyl-3-hydroxypyridine succinate) on the physical working capacity of athletes under the maximum intensity force loads characteristic of modern sports. Since pharmacology in sports is constantly searching for non-toxic drugs of the metabolithotropic origin that would have the ability to promote physical efficiency and slow down fatigue without toxic effects on the body, we have chosen for our research a drug based on succinic acid, which is a natural metabolite of the Krebs cycle. It has been shown that the armadin long preparation, when applied on a course for three weeks, positively affects the parameters of special working capacity associated with the improvement of the oxygen-transport function of blood. The metabolic basis of this phenomenon is the inhibition of a decrease in the pH of the internal environment of the body with the subsequent development of lactate-acidosis and the ability of the armadin long drug to accelerate the processes of angiogenesis, and, accordingly, the transport of oxygen to the athlete’s working muscles. The intensity of the formation of new growth factor (VEGF). Such data substantiate the expediency of the use of succinic acid-based agents to prevent negative metabolic changes and to slow down the onset of fatigue in athletes under intense physical loads.